2019
DOI: 10.1002/chem.201902444
|View full text |Cite
|
Sign up to set email alerts
|

Isotope and Hydrogen‐Bond Effects on the Self‐Assembly of Macroions in Dilute Solution

Abstract: We report on the disparity in the assembly behavior of four types of nano-sized macroions induced by isotopic substitution of protium (H) to deuterium (D) in solvents. Macroions with modest charge density can self-assemble into single-layer,h ollow,s pherical "blackberry"-type structures, with larger assembly sizes representings tronger attractions among the macroions. Kinetically,a ll assembly processes becomes lower in D 2 Ot han in H 2 O. Thermodynami-cally,t he polyoxometalate {SrPd 12 }, the uranium cage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…(8) POMs are valuable models for studying structure-size-property relations such as aggregation behavior in solution because they are larger than most inorganic complexes but smaller than colloids and are dissolvable as macroanions in various solvents. (9) Geochemically important POMs have been preserved in 42 POM minerals (10,11) and are likely important in metal transport in various geochemical and environmental systems. (12) Despite the wide-ranging aforementioned significance of POMs extending from basic scientific interest to sustainable energy applications, little is known about their thermodynamics and stabilities in various systems.…”
Section: Introductionmentioning
confidence: 99%
“…(8) POMs are valuable models for studying structure-size-property relations such as aggregation behavior in solution because they are larger than most inorganic complexes but smaller than colloids and are dissolvable as macroanions in various solvents. (9) Geochemically important POMs have been preserved in 42 POM minerals (10,11) and are likely important in metal transport in various geochemical and environmental systems. (12) Despite the wide-ranging aforementioned significance of POMs extending from basic scientific interest to sustainable energy applications, little is known about their thermodynamics and stabilities in various systems.…”
Section: Introductionmentioning
confidence: 99%
“…For all samples, the sizes of the blackberry structures (shown by CONTIN analysis) and the rate and activation energy of the assembly (calculated from the change of I 90 over time, Table S1) show no significant difference, except for the slightly faster assembly rate in urea. As urea is a strong hydrogen-bond disruptor, , which would interfere with the intermolecular hydrogen bonds, this slight rate increment indicates that the hydrogen bonds contributed slightly to the inter-{Mo 72 Fe 30 } attraction. , For weaker hydrogen-bond acceptors, e.g., oxoacid (NO 3 – , ClO 4 – , SO 4 2– ) anions, the blackberry formation rate has no significant difference. Therefore, the hydrogen bond is not the major driving force contributing to co-ion effects for small co-ions on the self-assembly of {Mo 72 Fe 30 }.…”
Section: Resultsmentioning
confidence: 94%
“…The influence of co-ions on {SrPd 12 } does not follow the trend in the Hofmeister series. The divergence among different co-ions may come from their roles on affecting the intermolecular hydrogen bonds and hydrophobic interaction. Previous study showed that the rate-determining step for the self-assembly is oligomer formation at the early stage. , The co-ions may compete with {SrPd 12 } at this stage via intermolecular interaction (for oxoacid ions, most likely a hydrogen bond) and slow down the oligomer formation, leading to lower assembly rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations